For real? Epistemic trust within online environments and the lures of conspiracy thinking - Schmidt-Boddy, Philipp; Vespermann, Daniel; Melichar, Gustav; Fuchs, Thomas (Human studies, 2026)
This paper examines how interactions within online environments affect the experience of shared reality by eroding trust. Trust has often been described as the ‘glue’ of society, essential not only for personal relationships, groups, and institutions but also for the very fabric of shared reality. One of its forms, epistemic trust, is of particular importance as it concerns the acquisition, acceptance, and establishment of shared knowledge, as well as the dynamics that sustain it. As online environments reshape our social interactions, they also modify significant conditions for epistemic trust—its requirements, incentives, and challenges. The aim of the paper is to illustrate these modifications, showcasing how online environments affect the various dimensions of epistemic trust that significantly shape how we experience shared reality. The paper unfolds in four steps. First, we present and discuss central cognitive and affective dimensions of epistemic trust and illustrate how it forms an inextricable aspect of social life and our sense of a shared reality (“Section 1: Epistemic trust and the experience of shared reality”). Second, we briefly present and discuss the phenomenon of conspiracy theories (“Section 2: The case of conspiracy theories”), and argue that their central features amount to a significant modification of our practices of epistemic trust (“Section 3: Epistemic trust and the experience of shared reality in the context of conspiracy theories”). Against this backdrop, we finally suggest that structural and phenomenological features of online environments can create epistemic scenarios that increase susceptibility to conspiratory mentalities and corresponding epistemic trust dynamics. We conclude that online environments may challenge our sense of a shared reality by shifting our propensities for epistemic trust (“Section 4: How online environments favor the development of conspiracy thinking”).
Gesehen am 04.02.2026